Teaching discourses and practices about diversity in rural basic multigrade classrooms - Maurial Mackee, Mahia (2022)
This case-study analyzes the coherence between discourses and teachers’ practices of teachers to attend diversity of their students in Language course. It includes the visit to 6 Educational Institutions in which the authors completed 14 classrooms’ observations and 12 teachers’ interviews from rural public multigrade elementary schools in Tacna and Ayacucho Regions of Peru. There is a partial coherence between discourse and practice in attention to children’s diversity by grade or cycle, but not by gender, age, cultural styles and learning rhythms. Analysis’ categories: a) Teachers discourse about i) Students’ diversity; ii) Multigrade teaching in response to students’ diversity and c) Teachers’ practices in multigrade class-room towards diversity.